INTERPRETASI TUTUPAN LAHAN DI KESATUAN PENGELOLAAN HUTAN LINDUNG MODEL UNIT XIV TOBA SAMOSIR - Ade Putri Nugraha Harahap; Rahmawaty Rahmawaty; Riswan Riswan (Program studi Kehutanan USU, 2016)
Land Cover information is very important for the existence of a community forest management to organize the forest management based on the Ministry of Environtment Forestry decision; such as structuring and preparation of the forest management plans, forest utilization in terms of monitoring and control the licence holder, forest utilization in certain region, forest rehabilitation and reclamation, forest protection and nature conservation. The aimed of this study to classify land cover types. This study was conducted in April to May 2015 in Forest Management Unit XIV Toba Samosir. The method of remote sensing by using Landsat image 8 in 2014. The result of this study showing that there were land cover types in KPHL Unit XIV Toba Samosir. They were secondary dryland forest, forest plantation, dryland farming, shrubs, and water. Dryland Agriculture type was the most dominating the land cover with 36,89%. Overall accuracy in this study is 0,98%. Keywords : Forest Management Unit XIV Toba Samosir, Image of landsat 8, Land Cover, Mapping